2-Imidazole as a Substitute for the Electrophilic Group Gives Highly Potent Prolyl Oligopeptidase Inhibitors - Pätsi Henri T; Kilpeläinen Tommi P; Auno Samuli; Dillemuth Pyry MJ; Arja Khaled; Lahtela-Kakkonen Maija K; Myöhänen Timo T; Wallén Erik AA (Amer Chemical Soc, 2025)
Different five-membered nitrogen-containing heteroaromatics in the position of the typical electrophilic group in prolyl oligopeptidase (PREP) inhibitors were investigated and compared to tetrazole. The 2-imidazoles were highly potent inhibitors of the proteolytic activity. The binding mode for the basic imidazole was studied by molecular docking as it was expected to differ from the acidic tetrazole. A new putative noncovalent binding mode with an interaction to His680 was found for the 2-imidazoles. Inhibition of the proteolytic activity did not correlate with the modulating effect on protein-protein-interaction-derived functions of PREP (i.e., dimerization of alpha-synuclein and autophagy). Among the highly potent PREP inhibiting 2-imidazoles, only one was also a potent modulator of PREP-catalyzed alpha-synuclein dimerization, indicating that the linker length on the opposite side of the molecule from the five-membered heteroaromatic is critical for the disconnected structure-activity relationships.